Prevalence of overweight, obesity, underweight and normal weight in French youth from 2009 to 2013 - Vanhelst, Jérémy; Baudelet, Jean-Benoît; Fardy, Paul S; Béghin, Laurent; Mikulovic, Jacques; Ulmer, Zékya (Public health nutrition, 2017)
To determine the prevalence of underweight, overweight and obesity in French youth from 2009 to 2013 and to determine if there are differences in weight categories according to socio-economic status. Cross-sectional study performed in different regions of France. Physical measures included weight, height and BMI. Underweight, overweight and obesity were defined according to age- and sex-specific BMI cut-off points from the International Obesity Task Force. France. Children and adolescents (n 9670; 4836 boys, 4834 girls) from the French national BOUGE Program between 2009 and 2013. The prevalence of obesity was higher in boys than girls (P0·05) and remained unchanged in boys (7·1-7·3 %) between 2009 and 2013. Overweight and obesity were higher in low socio-economic families (P<0·0001). Findings suggest that the prevalence of overweight was stable although high in French children and adolescents, while the prevalence of obesity increased significantly. Changes in underweight, although not significant, were high in girls and merit further attention. Improving public health interventions, especially in high-risk low socio-economic populations, may help to modify the behaviour that contributes to underweight, overweight and obesity in young boys and girls.